Economics in perspective : a critical history - Galbraith, John Kenneth, 1908-2006 (Princeton University Press, 2017)
The author examines the development of economics from ancient Greece to the modern welfare state, arguing that its "history cannot be understood apart from the circumstances that shaped the economic beliefs of the time, including the powerful influences that bent those beliefs to what best served the financial advantage of those who espoused them.